Effects of Bulgarian bag exercises on power and shot speed for handball players - Amany, F. (Science, Movement & Health, 2017)
Handball is one of the most popular team sports worldwide. According to the International Handball Federation, about 800 000 teams from 183 handball associations are registered (IHF, 2013). In recent years, handball has received increased attention in research literature, and several authors have investigated the physical demands for elite players. One of the most ultimate extreme fitness tool is Bulgarian Training Bag. The unique shape of the bag designed to allow for both upper and lower body training while emphasizing superior grip strength at all times. The purpose of this study was to investigate the effects of Bulgarian bag exercises on power and shot speed for handball players. Methods. Twenty handball female players were randomly allocated to receive either an 8-week intervention of the of Bulgarian bag exercises (n = 10) and a control group receiving 8-week of normal training only (n = 10). The radar speed gun monitored jump shots with a 2 m run -up in randomized order. The data collected before and after the program for the two groups. Results. Statistical analyses showed that: The experimental group had significantly higher than the control group in shot speed .The experimental group had significantly higher than the control group in physical variables (strength-power) Conclusions. Under the conditions of our study, complex training to 8 weeks resulted in an increase in power and shot speed for handball female players. These results have to be taken into account by coaches in order to better understand and implicated of these concepts for technical effects of training